2019
DOI: 10.1371/journal.pone.0215972
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the costs of cholera illness and cost-effectiveness of a single dose oral vaccination campaign in Lusaka, Zambia

Abstract: Introduction In 2016, for the very first time, the Ministry of Health in Zambia implemented a reactive outbreak response to control the spread of cholera and vaccinated at-risk populations with a single dose of Shancol—an oral cholera vaccine (OCV). This study aimed to assess the costs of cholera illness and determine the cost-effectiveness of the 2016 vaccination campaign. Methodology From April to June 2017, we conducted a retrospective cost and cost-effectiveness ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…The studies in Juba, Sudan, and Zambia established the immediate population level impact of this practical outbreak response approach. In addition, a cost-effectiveness analysis of the single dose OCV reactive campaign in densely populated areas of Lusaka, Zambia showed that the single dose vaccine approach was cost-effective [60].…”
Section: Effectiveness Studies In Outbreak Settingmentioning
confidence: 99%
“…The studies in Juba, Sudan, and Zambia established the immediate population level impact of this practical outbreak response approach. In addition, a cost-effectiveness analysis of the single dose OCV reactive campaign in densely populated areas of Lusaka, Zambia showed that the single dose vaccine approach was cost-effective [60].…”
Section: Effectiveness Studies In Outbreak Settingmentioning
confidence: 99%
“…Because of this, it has not been possible to take into account both single- and two-dose regimen effects in the same modelling using VICE for the calculations of cost-effectiveness ratios. Since reasonable evidence suggests that a single dose of oral cholera vaccine provides moderate protection from cholera [ 43 46 ], the current findings could have understated the effects and cost-effectiveness ratios. Finally, some costs were not assessed.…”
Section: Limitationsmentioning
confidence: 95%
“… 13 Furthermore, a PubMed search in September 2019 yielded three more studies published subsequently—one each from Malawi, 14 Ghana 15 and Zambia. 16 Data from these five studies were extracted and used as inputs in the analysis.…”
Section: Methodsmentioning
confidence: 99%
“… 13 While the study in Zambia did not give an exact average, we were able to estimate the average based on the survey results. 16 The ranges of the lost days were calculated based on the range derived from the study in Tanzania, where the variability of 20% was observed. The lost days were then multiplied by the average gross domestic productivity (GDP) per capita 18 to derive total productivity loss per cholera episode.…”
Section: Methodsmentioning
confidence: 99%